Improving Learning Outcomes On Moral Aspects With Demonstration Method In Class IX Smpn 47 Seluma - Inderiyah, Anis (Multidisciplinary Journals, 2025)
This Classroom Action Research (PTK) was conducted to improve Islamic Religious Education learning at SMPN 47 Seluma. The learning was designed using demonstration and role-playing methods. In even semester 2023/2024 Data collection was carried out through observation, written tests, interviews and questionnaires to students. Observations were made to observe the demonstration and role-play activities of students. Written tests were conducted to determine the improvement of learning outcomes and the percentage of students. Interviews were conducted to find out the extent of the learners' response to learning. Questionnaires were conducted to determine the learning atmosphere and teacher activities during the learning process. In accordance with the problems and research objectives, the methodology used is class action research conducted in 2 cycles. The research sample was class IX students of SMPN 47 Seluma, consisting of 30 students, 19 women and 11 men. This class action research applies demonstration method learning with the aim of: (1) To find out how likely the demonstration method can improve the learning outcomes of students (2) to find out the response of students (3) to find out the atmosphere of learning and learning. The results of the research findings obtained are: (1) The activity of students in learning shows an increase from cycle to cycle. In cycle I, students‘ activities showed a score of 74.7%, then in cycle II it increased to 84.1%, (2) Students’ responses to learning with this demonstration method, they stated that it was very fun, not bored and easy to understand. (3) The learning outcomes of students have increased which is reflected in the acquisition of percentages. The acquisition of the percentage value in cycle I was 36.7% with the completeness of 11 students, in cycle II it increased to 64% with the completeness of 19 students. Based on the research findings, it can be concluded that through the application of role demonstration method learning can improve student learning outcomes.